Effectiveness of the 2010–2011 seasonal influenza vaccine in preventing confirmed influenza hospitalizations in adults: A case–case comparison, case-control study - Puig-Barberà, J. (Vaccine, 2012)
INTRODUCTION: We estimated influenza vaccine effectiveness (IVE) to prevent laboratory-confirmed influenza-related hospitalizations in patients 18 years old or older during the 2010–2011 influenza season. METHODS: We conducted a prospective case-control study in five hospitals, in Valencia, Spain. Study subjects were consecutive emergency hospitalizations for predefined conditions associated with an influenza-like illness episode <8 days before admission. Patients were considered immunized if vaccinated ≥14 days before influenza-like illness onset. Cases were those with a real time reverse transcriptase polymerase chain reaction (RT-PCR) positive for influenza and controls were RT-PCR positive for other respiratory viruses. Adjusted IVE was estimated as 100 × (1 − adjusted odds ratio). To account for indication bias we computed adjusted IVE for respiratory syncytial virus related hospitalizations. RESULTS: Of 826 eligible hospitalized patients, 102 (12%) were influenza positive and considered cases, and 116 (14%) were positive for other respiratory viruses and considered controls. Adjusted IVE was 54% (95% confidence interval, 11–76%). By subgroup, adjusted IVE was 53% (4–77%) for those with high-risk conditions, 59% (16–79%) for those ≥60 years of age, and, 54% (4–79%) for those ≥60 years of age with high-risk conditions. No influenza vaccine effect was observed against respiratory syncytial virus related hospitalization. CONCLUSION: Influenza vaccination was associated with a significant reduction on the risk of confirmed influenza hospitalization, irrespective of age and high-risk conditions.